Evaluation of Quality Protein Maize (QPM) Genotypes under Rainfed Mid Hill Environments of Nepal - Upadhyay, S. R.; Gurung, D. B.; Paudel, D. C.; Koirala, K. B.; Sah, S. N.; Prasad, R. C.; Pokhrel, B. B.; Dhakal, R. (Nepal Journal of Science and Technology, 2010)
Maize (Zea mays L.) is the second most important staple food crop after rice and a major food crop of the resource poor people in the hills of Nepal. Prevailing normal maize (non-QPM) is deficient in two essential amino acids, lysine and tryptophan. The majority of hill farm families are suffering from protein malnutrition as their major diet is maize and cannot afford animal protein. QPM contains opaque-2, a single gene mutation that alters the protein composition of the endosperm portion and nearly double the essential amino acids concentrations than the normal maize grain. The biological value of protein in QPM maize is about 80%, that of milk is about 90% and in normal maize (non-QPM) is about 45% only. A series of experiments were conducted in RCB Design during 2004/2005 summer season and superior genotypes selected and promoted from Observation Nurseries to IYT and CVT (Coordinated Varietal Trial) respectively. CVTs were evaluated across mid-hills of Nepal. Based on four environmental mean results in CVT: the genotype S99TLWQ- HG-AB (QPM maize) produced the highest mean grain yield (4899 kg ha-1) followed by Population 44 C10 (4552 kg ha-1) and Manakamana-3 (4436 kg ha-1) respectively. However, most of the tested QPM genotypes were at par with improved check for grain yield production and significantly highest grain yielder than the farmres’ variety (local check). Concluding results revealed that the genotype S99 TLWQ-HG-AB performed very well across the mid hills. Findings of the present study will help to reduce protein malnutrition problem in the hills of Nepal. Key words: GGE-biplot; Genotype x environment interaction; Normal maize; Open pollinated varieties (OPV); Quality protein maize (QPM). DOI: 10.3126/njst.v10i0.2803 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 9-14